Influence of Playability on Perceived Game Software Quality: A Comparison Between Chinese and South Korean Gamers - Jiang, Jialei; Wong, Philip Pong Weng*; Wang, Lei (SAGE Publications, 2023)
The usability of ISO/IEC 25000 series SQuaRE and other existing software quality models seems unsuitable for unique software products such as game software. This study revealed that playability has a higher predictive capacity than usability for evaluating game software quality using a survey methodology involving 344 Chinese respondents and 142 South Korean respondents. Specifically, dimensions of playability in terms of enjoyable, exciting, fun, interesting, relaxing, novel, creative, convenient, curious, fantastic, stimulating, splendid, effective and attractive positively influenced both Chinese and South Korean game software users’ satisfaction. In addition, results show that there is a significant difference between Chinese and South Koreans in playability dimensions such as exciting, relaxing, novel, creative, convenient, curious, stimulating, splendid and attractive. This study extends the existing knowledge on how playability influenced game software users’ satisfaction and software quality, and limitations were also highlighted.